2008
DOI: 10.1103/physreve.78.011305
|View full text |Cite
|
Sign up to set email alerts
|

Birth and growth of a granular jet

Abstract: The interaction between fine grains and the surrounding interstitial gas in a granular bed can lead to qualitatively new phenomena not captured in a simple, single-fluid model of granular flows. This is demonstrated by the granular jet formed by the impact of a solid sphere into a bed of loose, fine sand. Unlike jets formed by impact in fluids, this jet is actually composed of two separate components, an initial thin jet formed by the collapse of the cavity left by the impacting object stacked on top of a seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
44
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 30 publications
6
44
1
Order By: Relevance
“…For fine powders in air, granular jets and cavity collapse occur during impact [12,13]. Subsequent studies showed that the ambient pressure of the interstitial fluid (air) is an important element for the observed fluid-like behavior [14][15][16], while for denser packing the impact penetration is much reduced [17]. However, the question of the physical mechanisms and control parameters that give rise to such a wide variety of phenomena is still largely open.…”
mentioning
confidence: 99%
“…For fine powders in air, granular jets and cavity collapse occur during impact [12,13]. Subsequent studies showed that the ambient pressure of the interstitial fluid (air) is an important element for the observed fluid-like behavior [14][15][16], while for denser packing the impact penetration is much reduced [17]. However, the question of the physical mechanisms and control parameters that give rise to such a wide variety of phenomena is still largely open.…”
mentioning
confidence: 99%
“…A different explanation relies on the presence of interstitial gas throughout the bed. In situations where the gas permeability is low, i.e., fine-grained beds, the gas is effectively trapped during the short impact duration and can resist global packing density changes [15]. For loose packings this leads to a response whereby a large portion of the bed surrounding the impact behaves similar to an incompressible liquid, allowing the impactor to sink in [18].…”
mentioning
confidence: 99%
“…Probing the resulting combination of liquidand solid-like properties a number of recent studies investigated the impact of a large object into a bed of dry grains. These studies focused on issues such as the drag on the impacting object [1-6], crater formation [7-10] the corona-like splash formed immediately after the impactor hits the bed surface [10], and the subsequent jet of grains formed by the collapse of the cavity left by the impactor [11][12][13][14][15][16]. So far however, almost all work considered the limit of loosely packed, marginally stable beds that readily compact in response to perturbations.…”
mentioning
confidence: 99%
“…The focus here was on impact of non-Newtonian fluids, but investigations of many other research topics, such as liquid drop breakup 19,20 , granular jets 21 , and liquid drop coalescence 22 , benefit from a similar technique. Such experimental approach makes it possible to image microscale phenomena and at the same time obtain insights into the accompanying dynamics at the scale of microseconds, a regime that is challenging for conventional imaging methods.…”
Section: Discussionmentioning
confidence: 99%